Study on the dielectric properties of Al2O3/TiO2 sub-nanometric laminates: effect of the bottom electrode and the total thickness. (19th January 2018) - Ben Elbahri, M; Kahouli, A; Mercey, B; Lebedev, O; Donner, W; Lüders, U
Abstract: Dielectrics based on amorphous sub-nanometric laminates of TiO2 and Al2 O3 are subject to elevated dielectric losses and leakage currents, in large parts due to the extremely thin individual layer thickness chosen for the creation of the Maxwell–Wagner relaxation and therefore the high apparent dielectric constants. The optimization of performances of the laminate itself being strongly limited by this contradiction concerning its internal structure, we will show in this study that modifications of the dielectric stack of capacitors based on these sub-nanometric laminates can positively influence the dielectric losses and the leakage, as for example the nature of the electrodes, the introduction of thick insulating layers at the laminate/electrode interfaces and the modification of the total laminate thickness. The optimization of the dielectric stack leads to the demonstration of a capacitor with an apparent dielectric constant of 90, combined with low dielectric loss (tan δ ) of 7 · 10 −2 and with leakage currents smaller than 1 × 10 −6 A cm −2 at 10 MV m −1 .